Applying Critical Social Theories to Family Therapy Practice - McDowell, Teresa (Springer, 2015)
This volume applies critical social theories to family therapy practice, using sociopolitical context for a clearer focus on the power dynamics of couple and family relationships. Its decolonizing approach to therapy is shown countering the pervasive cultural themes that grant privilege to specific groups over others, feeding unequal and oppressive relationships that bring families and couples to treatment. Therapy is shown here as a layered and nuanced process, with practitioners developing an ethical human rights perspective toward their work as they aid clients in negotiating for greater justice and equity in their relationships. The book bridges theory and practice by giving readers these essential tools